(untitled) (London Journal of Engineering Research, 2025)
Conventional electrochemical processes with voltages of a few Volts only occur in an electrolyte solution, but with high DC voltage electrode reactions can still occur in non-aqueous electrolyte, even distilled water. Electricity not only converts to heat, which increases the temperature of the water environment, but also performs anodic electrochemical reactions such as dissolving metals or generating oxygen (Me®Men++ne; 2H2O®O2+4H+) and generating hydrogen gas on the cathode (2H2O®H2+2OH). The gaseous environment formed from the electrochemical reactions on the electrodes with high electric, magnetic and suitable temperature conditions will appear plasma on the electrodes – the ionized state of materials. The reactions in the plasma state will generate many strong reactive agents such as electrons, atoms of H, O, O3 as well as free radicals H•, O•, OH•…Simultaneous dispersion into solution of agents formed by eletrochemical processes with DC high-voltage and plasma reactions creates a variety of application possibilities.